THE ROLE OF PRIVATE INITIATIVES IN OVERCOMING HOMELESSNESS: COOPERATION WITH SECTION 8 AND LOCAL HOUSING AUTHORITIES IN THE USA - Кравченко, Микита (SWorldJournal, 2026)
The paper analyzes the mechanism for supporting low-income households in the United States within the framework of the Section 8 Housing choice voucher program of the Department of Housing and Urban Development. The indicators of federal funding of the pr